Pengaruh Testimoni Desain Produk dan Harga Terhadap Minat Beli Smartphone Android Infinix di Shopee (Studi Kasus Perumahan Griya Asri 2 Kabupaten Bekasi) - Muhammad Elzan Musyafa; Hadita Hadita; Neng Siti Komariah; Novita Wahyu Setyawati; Jumawan Jumawan (Fibonacci: Jurnal Ilmu Ekonomi, Manajemen dan Keuangan, 2025)
This study aims to analyze the influence of testimonials, product design, and price on the purchase intention of Infinix smartphones on Shopee, focusing on consumers in Griya Asri 2 Housing, Bekasi Regency. The research method used is quantitative with a descriptive and verification approach. Data collection techniques are carried out through a survey with a questionnaire on samples selected using the random sampling method. Data analysis uses multiple linear regression to test the relationship between independent variables (testimonials, product design, and price) with the dependent variable (purchase intention). The results of the study show that testimonials have a significant influence on purchase intention, where positive reviews from previous consumers can increase product credibility. Attractive and functional product design also contributes to increasing consumer appeal to Infinix products. In addition, competitive prices are a major factor in purchasing decisions, where consumers tend to choose products with values that match the price offered. Simultaneously, these three variables have a significant influence on consumer purchase intention, indicating that the combination of testimonials, product design, and price can create a more effective marketing strategy in increasing sales of Infinix smartphones on Shopee.